2021
DOI: 10.1021/acs.jpcc.0c09900
|View full text |Cite
|
Sign up to set email alerts
|

Dirac Semimetals in Homogeneous Holey Carbon Nitride Monolayers

Abstract: In this work, we propose four novel holey carbon nitride monolayer C7N3, C10N3, C13N3, and C19N3 stoichiometries intriguingly behaving as ideal 2D Dirac semimetals whose Dirac cones are rightly located at the Fermi level. Moreover, the results of Gibbs free energies, phonon dispersions, ab initio molecular dynamics, and linear elastic constants indicate that their stabilities are comparable with the already-synthesized 2D carbon nitride materials. The Dirac cones of the systems originate from the hopping betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Recently, Tan et al have theoretically designed C x N 3 (x = 7, 10, 14, 19) monolayers with excellent logistics and proposed all possible synthetic routes for experimental fabrication. Taking inspiration from their work, we have successfully reproduced the geometries proposed by Tan et al [22] These four monolayers are found to have similar physical properties as well as almost same level of thermodynamic stability. Thus, we have decided to analyze one small and one large system to find the electrochemical performance.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Recently, Tan et al have theoretically designed C x N 3 (x = 7, 10, 14, 19) monolayers with excellent logistics and proposed all possible synthetic routes for experimental fabrication. Taking inspiration from their work, we have successfully reproduced the geometries proposed by Tan et al [22] These four monolayers are found to have similar physical properties as well as almost same level of thermodynamic stability. Thus, we have decided to analyze one small and one large system to find the electrochemical performance.…”
Section: Resultsmentioning
confidence: 55%
“…In this circumstances, it is interesting to explore the electrochemical performance along with the electrode utility of these newly designed carbon nitride (C x N 3 ; x = 10, 19) monolayers having perfectly planar porous geometry with Dirac semimetallicity in their electronic structure. [22] In order to have clear understanding of the electrochemical performance of newly designed C x N 3 monolayers, herein we have performed first-principles density functional theory (DFT) calculations to predict the potential of C x N 3 monolayers as anode material in LIBs. In this article, employing simple thermodynamic treatment we have re-optimized the C x N 3 monolayers and checked their thermal stability using ab-initio molecular dynamics simulation (AIMD) at 500 K for 5 ps with a time step of 1 fs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to manufacture high-performance miniaturized devices, such as ultrathin channel field-effect transistors 2,3 (FETs), suitable band gaps, high carrier mobility and high stability are essential for 2D materials. [4][5][6][7][8][9] So far, graphene, 1 black phosphorene and two-dimensional transition metal dichalcogenides (TMDs) have received extensive research attention due to their excellent electronic properties. Graphene's two-dimensional planar structure and ultra-high carrier mobility make it very promising in the field of field-effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular precursors can be fabricated by the self-assembly of melamine, urea, barbituric acid, etc., by utilizing the hydrogen bonding and π–π interaction between these C,N-containing monomers. The C/N ratio of carbon nitride can be conveniently adjusted by selecting carbon- or nitrogen-rich monomers for supramolecular precursors, which strongly influences the electronic structure, band gap, and band edges position of the obtained carbon nitride …”
Section: Introductionmentioning
confidence: 99%
“…17−19 The C/N ratio of carbon nitride can be conveniently adjusted by selecting carbon-or nitrogen-rich monomers for supramolecular precursors, which strongly influences the electronic structure, band gap, and band edges position of the obtained carbon nitride. 20 To achieve both high polymerization degree and optimum band structures of carbon nitride, the integration of ionothermal technology and supramolecular precursors seems to be promising, which, however, has never been reported to our knowledge. Addressing this, a supramolecular precursor CMBA was first synthesized through the molecular-level selfassembly of barbituric acid, melamine, and cyanuric acid, which was then ionothermally converted into a unique winered carbon nitride (WRCN) in the presence of salts (NaCl, KCl) under high temperature.…”
Section: ■ Introductionmentioning
confidence: 99%